Literary and religious practices in medieval and early modern India - Aquil, Raziuddin; Curley, David L. (Routledge, Taylor & Francis Group, 2017)
1. Sufi attitudes toward homosexuality : Chishti perspectives from South Asia / Scott Kugle -- 2. Religious sects, syncretism, and claims of antiquity : the Dashanami-Sannyasis and South Asian Sufis / Matthew Clark -- 3. Mingling of the oceans : a journey through the works of Dara Shikuh / Mridula Jha -- 4. Contested religious identities in Prannathi textual discourses during the reign of Emperor Aurangzeb / Sandhya Sharma -- 5. Ballads, public memory, and history in the littoral zone of Eastern Bengal / David L. Curley -- 6. The story of Jayamati's humiliation and death : reworking of the indigenous sources in Assamese historiography of the nineteenth and twentieth centuries / Sudeshna Purkayastha -- 7. Retelling medieval history for twentieth-century readers : encounter of a Hindu prince and a Sufi master in Khwaja Hasan Nizami's Nizami Bansuri / Mikko Viitamaki.